Motivation and Performance of Employees of Pokhara Based Internet Service Providers - Adhikari, Nabin Bahadur (Kalika Journal of Multidisciplinary Studies, 2023)
Employee motivation is one of the important factors that can help the employer to improve employees and organizational performance. This research paper aims to investigate the impact of motivation on employee performance in Pokhara based internet provider. This article is based on case study method in which ‘Pokhara Internet Private Limited’ was selected by following lottery method of sampling. The study sample size was about 90% (103) of the population which was randomly selected from each department of the Pokhara Internet Pvt. Limited with the help of employees name list provided by HR Department. The study applied empirical approach in which a survey questionnaire was used to collect quantitative data. For the fulfillment of research objective various statistical techniques has been applied. The hypothesis was set to test under some constraints. The statistical tool like descriptive statistic and inferential statistics like ANOVA, multiple linear regressions was applied for this regard the famous statistical software named SPSS-20 has been used. The results validated the research questions and proved statistically significant impact of employees’ motivation on their performance. Moreover, it is also known that female employees had high level of motivation in the sample institution.